Gold Mineralization in Ontario I - The Role of Banded Iron Formation - A. J. Macdonald (Canadian Institute of Mining, Metallurgy and Petroleum, 1984)
Gold deposits hosted by banded iron formation (BIF) in Ontario exhibit a marked association with localized zones of deformed and hydrothermally altered BI:F . Secondary sulphides and carbonates are conspicuous. Proposed carbonate-facies IF , or exhali tes, such as green carbonate in the Larder Lake camp and ankerite veins in the Porcupine Camp are structurally controlled, hydrothermally deposited zones of carbonate replacement and fissure filling. Gold precipitation from hyd r othermal fluids in strain-generated conduits may be due to (a) plating upon secondary sulphides, (b) pH change due to carbonatization of BIF or (c) destabilization of gold in solution due to sulphidation of BIF .